PENGARUH KERAGAMAN PRODUK, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA RENGGINANG IBU IMAM DI SITUBONDO - Mohammad Imam Ali Ghufran; Lita Permata Sari; Minullah Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Marketing plays a crucial role in a company and is highly connected to the external environment, particularly the market environment. This research aims to analyze the effect of product variety, product quality, and price on purchasing decisions with consumer satisfaction as an intervening variable at Rengginang Ibu Imam in Situbondo. The population in this study consisted of consumers of Rengginang Ibu Imam. The sampling method was determined using Probability Sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.2.8 application showed that: Product variety has a positive but not significant effect on consumer satisfaction; Product quality has a significant positive effect on consumer satisfaction; Price has a significant positive effect on consumer satisfaction; Product variety has a significant positive effect on purchasing decisions; Product quality has a significant positive effect on purchasing decisions; Price has a significant positive effect on purchasing decisions; Consumer satisfaction has a positive but not significant effect on purchasing decisions; Product variety has a positive but not significant effect on purchasing decisions through consumer satisfaction; Product quality has a positive but not significant effect on purchasing decisions through consumer satisfaction; Price has a positive but not significant effect on purchasing decisions through consumer satisfaction.